CHRISTIAN MOTIVES IN VASYL KOVALYUK’S PAINTING - Mishchenko , Iryna (Collection of scientific papers «ΛΌГOΣ», 2022)
Vasyl Kovalyuk (1956–2013) graduated from the department of artistic metal processing of the Vyzhnytsk School of Applied Arts [1] and mentioned Volodymyr Yugai, a painting teacher at the Kyiv studio [2], among those who had the greatest influence on his formation. Painting became the field in which the artist realized himself to the fullest. Turning to many genres, creating plot and abstract compositions, still lifes, the artist often chose biblical and evangelical motifs as the theme of his paintings, offering his own interpretation of eternal truths ("Two views of betrayal", 1999; "Joy and pain of the Mother of God", 1999; " The Thirteenth", 2000; "The Angel Behind My Window", 2001; "Straight Talk", 2004).